(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
In this article, the water content in the leaves of blackberry (rubus fruticosus) varieties cultivated in the central field of the Andijan Scientific Experimental Station of the Research Institute of Horticulture, Viticulture and Winemaking named after Academician Makhmud Mirzaev, located in the Izboskan district of Andijan region, was studied.